Lactic acid fermentation of Arthrospira platensis (spirulina) biomass for probiotic-based products - Niccolai, Alberto; Shannon, Emer; Abu-Ghannam, Nissreen; Biondi, Natascia; Rodolfi, Liliana; Tredici, Mario R. (Journal of applied phycology, 2019)
The first objective of this study was to evaluate the use of lyophilised biomass of the cyanobacterium Arthrospira platensis F&M-C256 as the sole substrate for lactic acid fermentation by the probiotic bacterium Lactobacillus plantarum ATCC 8014. After 48 h of fermentation, the bacterial concentration was 10.6 log CFU mL −1 and lactic acid concentration reached 3.7 g L −1 . Lyophilised A. platensis F&M-C256 biomass was shown to be a suitable substrate for L. plantarum ATCC 8014 growth. The second objective of the study was to investigate whether lactic acid fermentation could enhance in vitro digestibility and antioxidant activity of A. platensis biomass. Digestibility increased by 4.4%, however it was not statistically significant, while the antioxidant activity and total phenolic content did increase significantly after fermentation, by 79% and 320% respectively. This study highlights the potential of A. platensis F&M-C256 biomass as a substrate for the production of probiotic-based products.